Prevalence and Determinant Factors of Coronary Heart Disease Status in Patients with Heart Failure - Anwari Delmi; Dwi Laksono Adiputro; Dona Marisa; Alfi Yasmina (Berkala Kedokteran, 2021)
Abstract: As a cardiovascular disease, heart failure is one of prime mortality cause in the world. Coronary heart disease has a role in development of heart failure so that it becomes one of heart failure’s major clinical risk factor. This study aimed to calculate the prevalence of and identify the factors that influence coronary heart disease status of heart failure patients at Alamanda ward of RSUD Ulin Banjarmasin in 2016. Factors that were studied consisted of age, sex, family history of heart disease, smoking, diabetes mellitus, and hypertension. This study used analytical observation with cross-sectional approach on medical records that were obtained by purposive sampling method. The result showed 46.4% of 263 heart failure patients had coronary heart disease status. Multivariate analysis inferred hypertension as the factor that influences the coronary heart disease status of heart failure patients (OR = 1.98, 95% CI = 1.06 – 3.71, P = 0.033). Keywords: cardiovascular disease, heart failure, coronary heart disease, hypertension